(3GdaUd GdSGHY ef cJGH JYQja GdJWQjas - (3fhQ GdOjf CHh YHO Gddg MejOGf Hf jMji Hf MejOG GdbGSeis
(3ChdgG (B:s
(3bGd QVi Gddg Yfg , hCeG GdaUd GdSGHY hgh ai eYQaI GdMLL GdOGdI Ydi HWdGf GdEMGdI s
(3BNQgG (B:s
(3hai BjI OYhG Gddg eNdUjf dg GdOjf hfMh Pdc hGeG HXGgQ gPg GdMLL hEJaGbgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJGQjNs